2008
DOI: 10.1002/mrm.21445
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of myocardial viability in a small animal model: Comparison of MRI, SPECT, and PET

Abstract: Acute myocardial infarction (AMI) research relies increasingly on small animal models and noninvasive imaging methods such as MRI, single-photon emission computed tomography (SPECT), and positron emission tomography (PET). However, a direct comparison among these techniques for characterization of perfusion, viability, and infarct size is lacking. Rats were studied within 18 -24 hr post AMI by MRI (4.7 T) and subsequently (40 -48 hr post AMI) by SPECT ( 99 Tc-MIBI) and micro-PET ( 18 FDG). A necrosis-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…As a final assessment, however, TTC staining cannot be used for longitudinal follow-up. Several noninvasive imaging techniques attempted to measure infarct size and viability in rodents: single-photon emission computed tomography (11,36), positron emission tomography (27), magnetic resonance imaging (23,32,37), and contrast echocardiography (24). These options are not only invasive in nature as they require intravenous access and deep anesthesia, but, in addition, they are not widely available.…”
mentioning
confidence: 99%
“…As a final assessment, however, TTC staining cannot be used for longitudinal follow-up. Several noninvasive imaging techniques attempted to measure infarct size and viability in rodents: single-photon emission computed tomography (11,36), positron emission tomography (27), magnetic resonance imaging (23,32,37), and contrast echocardiography (24). These options are not only invasive in nature as they require intravenous access and deep anesthesia, but, in addition, they are not widely available.…”
mentioning
confidence: 99%
“…This method has been well known as the absolute threshold method [21,22]. MI size was defined as the percentage ratio of the area that was under the threshold value to the entire polar map area.…”
Section: Infarct-size Measurement (Methods A)mentioning
confidence: 99%
“…MI size was defined as the percentage ratio of the area that was under the threshold value to the entire polar map area. In previous studies, various absolute threshold values had been proposed (50-72 %) [21,22]. Higuchi et al [23] and Thomas et al [21] reported that decreased correlation coefficient was observed when took much lower threshold value in rodent model compared with the human study.…”
Section: Infarct-size Measurement (Methods A)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigations have shown that this is possible indeed with dedicated radionuclide imaging devices and radiotracers of myocardial blood flow and substrate metabolism. [1][2][3][4][5][6] Non-invasively observed regional radiotracer tissue concentrations were found to be closely correlated with those measured postmortem by tissue counting. Image-derived sizes of perfusion defects closely matched the infarct sizes determined postmortem by tissue staining techniques and thus were highly accurate.…”
mentioning
confidence: 99%